Beyond Charity: The Transformative Role of Social Fiqh in Advancing Substantive Rights for Persons with Disabilities - Akhmad Jalaludin; Agung Barok Pratama; Anindya Aryu Inayati (Institut Agama Islam Negeri Kerinci, 2025)
People with disabilities still do not get the same opportunities and special treatment according to the conditions experienced. Although the state guarantees equal rights for all citizens, its implementation for persons with disabilities is still not optimal, creating a gap between normative regulations and social reality. This research aims to analyze the issue through the perspective of social fiqh, which is the paradigm of Islamic law that emphasizes justice, empathy, and social inclusion, using a qualitative approach with a literature study design. Data was collected from academic works, official documents, and relevant policies, then analyzed by content analysis techniques through the systematic review method. The focus of the analysis is directed at mapping the principles of social fiqh that can be operationalized in answering the problem of marginalization of persons with disabilities. The results of the study show that the six main principles of social fiqh, namely al-'adālah (justice), at-tawādhu' (empathy), al-muwāsathah (social inclusion), ihyā' al-maṣāliḥ (empowerment), ḥifẓ al-nafs (care of the soul and mental health), and ta'līm wa tasyjīr (education and opportunity), not only provides theological legitimacy for the protection of the rights of persons with disabilities, but can also be used as a practical framework to encourage inclusive policies, economic empowerment, and adaptive access to education. The findings of this research can be an input for the government as a policy maker to formulate regulations that are more equitable for people with disabilities so that they can fulfill their social rights. In addition, it can be an input to the general public to be fair, empathetic and provide opportunities for socialization for people with disabilities so that they get equality and treatment as their conditions.